2021
DOI: 10.1002/adfm.202101632
|View full text |Cite
|
Sign up to set email alerts
|

Advanced High Entropy Perovskite Oxide Electrocatalyst for Oxygen Evolution Reaction

Abstract: A new type of lanthanum‐based high entropy perovskite oxide (HEPO) electrocatalyst for the oxygen evolution reaction is reported. The B‐site lattices in the HEPO consist of five consecutive first‐row transition metals, including Cr, Mn, Fe, Co, and Ni. Equimolar and five non‐equimolar HEPO electrocatalysts are studied for their OER electrocatalytic performance. In the five non‐equimolar HEPOs, the concentration of one of the five transition metals is doubled in individual samples. The performances of all the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
257
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 360 publications
(282 citation statements)
references
References 72 publications
(73 reference statements)
25
257
0
Order By: Relevance
“…It may be speculated that the deleterious influence of Cr on the transport properties may result from the presence of such cations in highly-distorted (high entropy) B-site sublattice, in which their tendency to trap small polarons becomes unusually high, which is not observed in classical systems, although confirming it would require further, dedicated studies. Relating the discussed observations with the reported excellent catalytic activity of La(Co,Cr,Fe,Mn,Ni)O 3−δ , exceeding that of the binary perovskites [25], shows a great potential of the high-entropy approach in generating unusual sets of physicochemical properties in (perovskite-type) materials.…”
Section: Electrical Conductivity Of the Ln(cocrfemnni)o 3−δ Seriessupporting
confidence: 59%
See 1 more Smart Citation
“…It may be speculated that the deleterious influence of Cr on the transport properties may result from the presence of such cations in highly-distorted (high entropy) B-site sublattice, in which their tendency to trap small polarons becomes unusually high, which is not observed in classical systems, although confirming it would require further, dedicated studies. Relating the discussed observations with the reported excellent catalytic activity of La(Co,Cr,Fe,Mn,Ni)O 3−δ , exceeding that of the binary perovskites [25], shows a great potential of the high-entropy approach in generating unusual sets of physicochemical properties in (perovskite-type) materials.…”
Section: Electrical Conductivity Of the Ln(cocrfemnni)o 3−δ Seriessupporting
confidence: 59%
“…Most importantly, the L7S3TM represents a rare case of Cr-containing air electrode material, which may contribute to its higher resistance to the deleterious Cr-poisoning effect, problematic for the state-of-the-art SOFCs [24]. The next study focused on the application of the La(Co,Cr,Fe,Mn,Ni)O 3−δ material as a potential catalyst for the oxygen evolution reaction (OER), essential for the water-splitting process [25]. The optimized, non-equimolar La(2Co,Cr,Fe,Mn,Ni)O 3−δ composition exhibited excellent performance, achieving OER overpotential of 325 mV at a current density of 10 mAcm −2 , greatly outperforming not only all conventional LaTMO 3 perovskites (TM = Co, Cr, Fe, Mn or Ni), but also state-of-the-art RuO 2 catalyst.…”
mentioning
confidence: 99%
“…High-entropy oxides (HEOs), single-phase “multi-component” solid solutions, possess numerous unique features such as inherent thermodynamic stability, high lattice distortion, high structure stability and superionic conductivity. 25 To date, high-entropy oxides have been applied as catalysts for CO oxidation, 26–30 oxidative desulfurization, 31 photocatalysis, 32 CO 2 hydrogenation, 33 CH 4 partial oxidation, 34 alcohol oxidation, 35 oxygen reduction reaction (ORR), 36 oxygen evolution reaction (OER), 37–39 etc. For example, Ting et al 37 reported a lanthanum-based high entropy perovskite oxide (HEPO) with an outstanding OER electrocatalytic performance (overpotential of 325 mV at 10 mA cm −2 and excellent stability after 50 h of testing).…”
Section: Introductionmentioning
confidence: 99%
“…25 To date, high-entropy oxides have been applied as catalysts for CO oxidation, 26–30 oxidative desulfurization, 31 photocatalysis, 32 CO 2 hydrogenation, 33 CH 4 partial oxidation, 34 alcohol oxidation, 35 oxygen reduction reaction (ORR), 36 oxygen evolution reaction (OER), 37–39 etc. For example, Ting et al 37 reported a lanthanum-based high entropy perovskite oxide (HEPO) with an outstanding OER electrocatalytic performance (overpotential of 325 mV at 10 mA cm −2 and excellent stability after 50 h of testing). In addition, Wang et al 38 synthesized a spinel-structured HEO, (Co, Cu, Fe, Mn, Ni) 3 O 4 , through a low-temperature solvothermal process and annealing, which shows an overpotential of 350 mV at 10 mA cm −2 when used as an OER catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Consequently, intensive research has been conducted to design cost-effective, efficient, stable, and earthabundant electrocatalysts to bring these energy technologies to cost parity. Currently, non-noble transition metal catalysts including layered double hydroxides LDH (e. g. FeNi LDH), [7] metal oxides (e. g. Co 3 O 4 ), [8][9][10][11][12][13] perovskites (e. g. LaSrFeO 3 ) [14,15] and high entropy materials (e. g. multi-metallic glycerate) [16,17] are reported as the most active non-precious OER catalysts in alkaline environment. In particular, the NiFe (oxy)hydroxide has revealed outstanding OER activity and stability.…”
Section: Introductionmentioning
confidence: 99%